Pengaruh Promosi yang Strategis dan Customer Relationship Management terhadap Kinerja Pemasaran Di Era Digital pada UMKM Kuliner Mie Gacoan Cabang Cikarang Selatan - Wita Safitri, Wita Safitri; Alya Aryanti Adilah; Jihan Khairunnisa; Alisya Sabrina Ningtyas; Ahmad Ramdani; Retno Purwani Setyaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasingly fierce competition for MSME businesses in the digital era requires businesses to adopt effective marketing strategies. Although 63.52% of e-commerce businesses use the internet for digital marketing, many MSMEs still have difficulty optimizing their strategies. This study aims to analyze the effect of strategic promotion and customer relationship management on marketing performance in the culinary MSME Mie Gacoan South Cikarang Branch in the digital era. This study uses a quantitative approach with an associative research type. The research sample consisted of 60 active employees of Mie Gacoan South Cikarang Branch who were selected using purposive sampling technique. The data were analyzed using multiple linear regression after collection through a closed questionnaire with a Likert scale. The results showed that partially, marketing performance was significantly influenced by strategic promotion and customer relationship management. Therefore, customer relationship management and strategic promotion have a positive and significant impact on marketing performance. These results provide important implications for culinary MSMEs in developing effective and sustainable digital marketing strategies in an era of increasingly fierce business competition.